Grade 10 English First Additional Language Learners’ Strategies For Past Tense Irregular Verb Inflection Mastery - Farisani Thomas Nephawe; Matodzi Nancy Lambani (STKIP Singkawang, 2021)
Abstract. The mastery of the irregular form of verbs in the past simple tense poses challenges to non-native learners of English all over the world. The objectives of this study were to identify the types of learners’ strategies useful for mastering the irregular verb inflection, to describe and evaluate them, and to establish why the English First Additional Language learners face difficulties in mastering those strategies. The study followed a quantitative research design. A questionnaire was used as an instrument for data collection from the respondents. Data were analysed using the Statistical Package for Social Sciences version 22 to ensure valid interpretations. Subsequent themes were placed in a table and a graph dealing with the inflection of irregular verbs. The target group of this study comprised 21 Grade 10 learners who were attending Dimani Secondary School in Limpopo Province, South Africa during the academic year 2021. From the data analysis, the initial study findings established that the respondents were incompetent in mastering the inflection of irregular verbs in the past simple tense when using the suppletion principle and the terminal consonants phoneme changes. The researchers used the grouping of common irregular verbs and the learning of irregular verbs in sentences strategies because learners were different and learned irregular verb inflection differently. Although it was previously found that learners could not understand the inflection of irregular verbs in the past simple tense, after having utilised these two strategies, the inflection of irregular verbs in the past simple tense improved with tremendous results. Keywords: Inflection; irregular verbs; past simple tense; strategies